Optimization of Pectin Extraction from Orange Pulp and Characterization of Compositional and Steady Shear Properties - Yilmaz, Mustafa Tahsin; Muslu, Asli; Karasu, Salih; Bozkurt, Fatih; Dertli, Enes (UNIV NAMIK KEMAL, 2017)
Pectin, which is one of the most important wastes of fruit juice industry, was extracted from orange pulp at optimum conditions (pH, time and temperature) and modified using pectinase. The effect of modification on the structural properties of pectin was monitored using Fourier transformed infrared spectroscopy (FTIR) and high performance liquid chromatography (HPLC) analyses. The bands at 1600-1800 cm(-1) which indicate the specific region and quality of pectin were detected using FTIR while galacturonic acid content was determined using HPLC. The results showed that the galacturonic acid content of pectin from orange pulp was determined to be 406.44 mg/g powder pectin while that of the modified pectin from the orange pulp was determined to be 465,34 mg/g powder pectin. In addition, flow properties of the pectin samples were determined using rheological analysis. The viscosity and viscoelastic properties of the modified pectin samples were revealed to be different from those of non-modified pectin samples. The consistency index values of unmodified and modified pectin samples were determined to be 0.0559 Pa.s(n) and 0.0046 Pa.s(n), respectively.
Keywords: orange pulp; pectin; modification; rheology; optimization; Agriculture